The new Congress - Mann, Thomas E.; Ornstein, Norman J.; American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1981)
This volume describes the United States Congress which is the meeting of the legislative branch of the Federal government of the United States as published in 1981. It is composed of the United States Senate and the United States House of Representatives.
Includes bibliographical references and index.
lje 23/01/2019
Loans
Keywords: Congress-United States; United States